Literature on Personnel Attitudes and Job Satisfaction: a Bibliometric Study - Eqbal, Monawwer; Masoom Raza, M. (Journal of Information and Knowledge, 2005)
The paper deals with the bibliometric study on Personnel Attitudes and Job Satisfaction. The aim of this study was to identify country, language, form, yearwise distribution and authorship pattern, ranking of authors and journals. Data was collected from Psychological Abstracts published from 1992-2001. The study reveals that USA has contributed highest number of papers, i.e., 59.53% and most dominant language was English and maximum number of articles were written by two authors. Most productive journal was Journal of Organisational Behaviour and maximum number of articles were published in ’ 1992 and most of the article dealt with Organisation Behaviour.